Comparison of lithosphere structure across the Orphan Basin–Flemish Cap and Irish Atlantic conjugate continental margins from constrained 3D gravity inversions - J. Kim Welford; Patrick M. Shannon; Brian M. O’Reilly; Jeremy Hall (2016)
Regionally constrained 3D gravity inversion results on the Orphan Basin–Flemish Cap and the Irish Atlantic conjugate continental margins are compared to investigate crustal structure, early rifting history and geological evolution of this part of the North Atlantic. The full-crustal density anomaly distributions provide some of the first depth images of how rifted structures compare along and across these conjugate margins. Broad similarities in crustal structure are identified with some noticeable differences, linked to rifting and crustal stretching processes. Extreme crustal thinning (stretching factors >3.5) is indicated beneath much of the southern Porcupine Basin, the western half of West Orphan Basin, the eastern half of Jeanne d’Arc Basin, the southeastern half of East Orphan Basin and in pockets beneath Rockall Basin. This appears to have resulted in the serpentinization (and possible exhumation) of mantle lithosphere on the Irish Atlantic and Flemish Cap margins but not beneath Orphan Basin. A simple evolution model is proposed for the early stages of rifting between the margins. It is suggested that ancient orogenic sutures played an important role in controlling the northward migration of rifting and the rotation and displacement of Flemish Cap out of Orphan Basin.